2019
DOI: 10.1017/pasa.2019.28
|View full text |Cite
|
Sign up to set email alerts
|

Incompressible analytical models for spinning-down pulsars

Abstract: We study a class of Newtonian models for the deformations of non-magnetized neutron stars during their spin-down. The models have all an analytical solution, and thus allow to understand easily the dependence of the strain on the star's main physical quantities, such as radius, mass and crust thickness. In the first "historical" model the star is assumed to be comprised of a fluid core and an elastic crust with the same density. We compare the response of stars with different masses and equations of state to a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 36 publications
(97 reference statements)
0
20
0
Order By: Relevance
“…Up to this point, the model is identical to that of Franco et al (2000). However, as recently done by Giliberti et al (2019), we allow for different densities in the two domains, ρ s in the elastic, solid crust, and ρ f = ρ s (1 + ∆ ρ) in the fluid core, which will be seen to make an important difference.…”
Section: Elastic Deformations In a Rotating Starmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to this point, the model is identical to that of Franco et al (2000). However, as recently done by Giliberti et al (2019), we allow for different densities in the two domains, ρ s in the elastic, solid crust, and ρ f = ρ s (1 + ∆ ρ) in the fluid core, which will be seen to make an important difference.…”
Section: Elastic Deformations In a Rotating Starmentioning
confidence: 99%
“…when they are not, i. e., in the Cowling approximation. In both equations, P and Q are functions whose precise form is unimportant for the present argument, and we have neglected higherorder terms in t and β (q and χ 2 , in the notation of Giliberti et al 2019), both of which are assumed to be small. From our equations ( 62) and ( 63), we see that the rigidity parameter depends on the fractional difference between the displacements for a purely fluid star ( β = 0) and a star with an elastic crust ( β 0),…”
Section: Effect Of the Cowling Approximationmentioning
confidence: 99%
See 2 more Smart Citations
“…A large b is conductive to produce large glitches. Crustquake model of NSs have been developed recently (Giliberti et al 2019(Giliberti et al , 2020Rencoret, Aguilera-Gómez, & Reisenegger 2021), which got challenged compared with observations. Previously, Baym & Pines found that, crustquakes of NSs encountered difficulty in explaining the frequent and large glitches (∆ν/ν ∼ 10 −6 ) in the Vela pulsar, unless the Vela pulsar is a lightest NS and glitch of size ∼ 10 −6 is an extremely unusual event (Baym & Pines 1971).…”
Section: The Starquake Scenariomentioning
confidence: 99%